2021
DOI: 10.15282/ijame.18.3.2021.13.0690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post-Injection Characteristics on the Combustion, Emission, and Performance in a Diesel-Syngas Reactivity Controlled Compression Ignition Engine

Abstract: This paper presents a numerical investigation of the separate effects of post-injection characteristics in a heavy-duty turbocharged direct injection diesel engine under pure diesel combustion (PDC) and diesel-syngas combustion (DSC) operating conditions. Converge CFD code was used coupled with a detailed n-heptane/toluene/PAH chemical kinetic mechanism (consists of 71 species and 360 reactions) for diesel-syngas dual-fuel combustion simulation. A total of 36 strategies based on the post-injection characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Pilot injection reduces NO x and PM emissions, reduces combustion noise and peak cylinder pressure and exhaust temperature. Final injection controls particulate emissions and exhaust gas temperature, the adequate value of which is necessary for the proper operation of exhaust after-treatment systems or turbochargers [25]. The authors of paper [26] found that final injection provides additional energy that improves mixing and accelerates soot oxidation at the end of the combustion process.…”
Section: Introductionmentioning
confidence: 99%
“…Pilot injection reduces NO x and PM emissions, reduces combustion noise and peak cylinder pressure and exhaust temperature. Final injection controls particulate emissions and exhaust gas temperature, the adequate value of which is necessary for the proper operation of exhaust after-treatment systems or turbochargers [25]. The authors of paper [26] found that final injection provides additional energy that improves mixing and accelerates soot oxidation at the end of the combustion process.…”
Section: Introductionmentioning
confidence: 99%